The social network - Fincher, David; Eisenberg, Jesse, 1983-; Garfield, Andrew, 1983-; Timberlake, Justin, 1981-; Hammer, Armie, 1986-; Minghella, Max, 1985-; Rudin, Scott, 1958-; De Luca, Michael, 1965-; Mezrich, Ben, 1969-; Columbia Pictures; Relativity Media; Trigger Street Productions (Los Angeles : Columbia Pictures Industries, 2011)
On a fall night in 2003, Harvard undergrad and computer programming genius Mark Zuckerberg sits down at his computer and heatedly begins working on a new idea. In a fury of blogging and programming, what begins in his dorm room soon becomes a global social network and a revolution in communication. A mere six years and 500 million friends later, Mark Zuckerberg is the youngest billionaire in history... but for this entrepreneur, success leads to both personal and legal complications.
Originally released as a motion picture in 2010.
Based on the book "The accidental billionaires" by Ben Mezrich.
Music by Trent Reznor, Atticus Ross ; director of photography Jeff Cronenweth ; screenplay by Aaron Sorkin.
Jesse Eisenberg, Andrew Garfield, Justin Timberlake, Armie Hammer, Max Minghella.
English dubbed into French, with subtitles in English for the hard of hearing, Arabic, Danish, Dutch, Finnish, French, Hindi, Norwegian, and Swedish.
Keywords: Zuckerberg, Mark, -- 1984- -- Drama; Saverin, Eduardo -- Drama; Facebook (Firm) -- History -- Drama; College students -- Drama; Feature films; Fiction films